Integrative analysis of the Trypanosoma brucei gene expression cascade predicts differential regulation of mRNA processing and unusual control of ribosomal protein expression - Antwi, Enoch; Haanstra, Jurgen R.; Ramasamy, Gowthaman; Jensen, Bryan; Droll, Dorothea; Rojas, Federico; Minia, Igor; Terrao, Monica; Mercé, Clémentine; Matthews, Keith; Myler, Peter J.; Parsons, Marilyn; et al. (BMC genomics, 2016)
Trypanosoma brucei is a unicellular parasite which multiplies in mammals (bloodstream form) and Tsetse flies (procyclic form). Trypanosome RNA polymerase II transcription is polycistronic, individual mRNAs being excised by trans splicing and polyadenylation. We previously made detailed measurements of mRNA half-lives in bloodstream and procyclic forms, and developed a mathematical model of gene expression for bloodstream forms. At the whole transcriptome level, many bloodstream-form mRNAs were less abundant than was predicted by the model.